Mokilese-English Dictionary - Harrison, Sheldon (PALI Language Texts-Micronesia, 1977)
This dictionary, the first formal compilation of words in Mokilese, contains about 5,000 entries with English glosses, grammatical information, and illustrative sentences for selected entries. It was created to fill the need for a dictionary in programs of bilingual education in the schools Mokilese children attend. This work will also be of use to anthropologists and linguists specializing in the Pacific.